2017
DOI: 10.1063/1.4973621
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the shrinking process of a bubble induced by laser metal ablation in water and experimental verification

Abstract: Laser ablation of a solid target immersed in liquid (such as water) has many important applications such as laser synthesis of nanoparticles, laser micromachining in water, and laser shock peening. Laser ablation of a solid target in water involves complicated physical processes. One important process often involved is the generation and evolution of a bubble in water and attached to the target surface, which may have significant effects on the target and the ambient water, and hence may greatly affect the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…47 A reasonable modelling can be done by the Rayleigh-Plesset (RP) equation, although it is known that RP does not well reproduce the collapse phase, and in particular the size of the bubble rebound. 48,49 The Gilmore equation incorporates water compressibility and condensation to reach a better agreement with bubble dynamics. [50][51][52] Nevertheless, we are mostly interested in the expanding bubble, where virtually no differences between the RP and Gilmore equations can be found with appropriate fitting parameters.…”
Section: Resultsmentioning
confidence: 99%
“…47 A reasonable modelling can be done by the Rayleigh-Plesset (RP) equation, although it is known that RP does not well reproduce the collapse phase, and in particular the size of the bubble rebound. 48,49 The Gilmore equation incorporates water compressibility and condensation to reach a better agreement with bubble dynamics. [50][51][52] Nevertheless, we are mostly interested in the expanding bubble, where virtually no differences between the RP and Gilmore equations can be found with appropriate fitting parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Tomko et al reported an asymmetric shrinking 35 . Contact angle hysteresis and bell-shaped bubbles in water have been observed 39 .…”
mentioning
confidence: 99%
“…An early laser-induced plasma is quickly quenched a few microseconds after the impact, leading to a vapour bubble [27][28][29][30][31][32] containing nanoparticles [33][34][35][36] . The bubble grows and collapses for first within a few hundreds of microseconds and finally leads to the release of the nanoparticles into the liquid 34,35 when the bubble fully collapses and disappears after a few oscillations 26,[37][38][39] . Persistent microbubbles are released during the collapse phase, which may shield a large portion of subsequent laser pulse in particular at high liquid viscosities 40 , and consist of chemical reaction products of the solvent and target, such as volatile carbohydrates 40 , hydrogen, oxygen and hydrogen peroxide 41 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These calculations supported the experimental evidence about the formation of oligoatomic clusters and also give possible explanations for wide size distributions observed for some LAL configurations. Also, finite element methods are being applied to study the cavitation bubble dynamics and, in particular, its collapse …”
Section: Figurementioning
confidence: 99%